1970
DOI: 10.3329/ujzru.v29i1.9461
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of cypermethrin, deltamethrin and nimbicidine on fecundity and egg viability of <i>Tribolium castaneum</i> (Herbst) (Coleoptera: Tenebrionidae)

Abstract: Fecundity and egg viability of Tribolium castaneum (Herbst) females were significantly (P<0.01) reduced by synthetic pyrethroids and an alkaloid containing insecticide nimbicidine. In control, the average number of eggs laid by each female/day was 12.18. The lowest number of eggs laid by each female/day was noted as 4.38 when combining nimbicidine with two pyrethroids i.e., cypermethrin and deltamethrin. The percentage of egg hatching without insecticide treatment was 95%. The lowest percent of egg hatching wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Several previous studies have shown that deltamethrin treatment suppressed egg production in T. castaneum ( 50 52 ). We also found that exposure of female beetles to LC 50 deltamethrin decreased the fecundity by 95.71% ± 1.20% ( t test, P -value = 5.8 × 10 −5 ) ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Several previous studies have shown that deltamethrin treatment suppressed egg production in T. castaneum ( 50 52 ). We also found that exposure of female beetles to LC 50 deltamethrin decreased the fecundity by 95.71% ± 1.20% ( t test, P -value = 5.8 × 10 −5 ) ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 92%